A practical guide to optical metrology for thin films - Quinten, Michael (Weinheim : Wiley-VCH ; Chichester : John Wiley [distributor], 2012)
A one-stop, concise guide on determining and measuring thin film thickness by optical methods. This practical book covers the laws of electromagnetic radiation and interaction of light with matter, as well as the theory and practice of thickness measurement, and modern applications. In so doing, it shows the capabilities and opportunities of optical thickness determination and discusses the strengths and weaknesses of measurement devices along with their evaluation methods. Following an introduction to the topic, Chapter 2 presents the basics of the propagation of light and other electromag.
7.7 Measurement of Critical DimensionsNumerics with Complex Numbers; A.1 Addition; A.2 Multiplication; A.3 Modulus; A.4 Division; A.5 Power n; A.6 Logarithm; A.7 Exponentiation; A.8 Trigonometric Functions; Fourier Transform; B.1 Linearity; B.2 Scaling; B.3 Shifting; B.4 Damping; B.5 Convolution; B.6 Plancherel Theorem and Parseval's Theorem; Levenberg-Marquardt Algorithm; Downhill Simplex Algorithm; References; Index.
Includes bibliographical references and index.
Print version record.
Keywords: Thin films -- Optical properties; SCIENCE -- Energy; SCIENCE -- Mechanics -- General; SCIENCE -- Physics -- General; Thin films -- Optical properties; Electronic books